Evidências de validade de critério do Zulliger Aplicação R-Otimizada para avaliar o Relacionamento Interpessoal e a Autoimagem em crianças vítimas de violência sexual - Implicações para o Envelhecimento Saudáve - Lima, Eduardo dos Santos de (2020)
Child sexual abuse is a public health problem that can cause harmful effects in the short and long term such as post-traumatic stress disorder and relationship problems, compromising healthy aging. Thus, there is a need for early and efficient evaluation, with the use of psychological instruments with psychometric properties. This dissertation aimed to search for evidence of criterion validity of the Zulliger, R-Optimized application, to assess the interpersonal relationship and self-image of children victims of sexual violence. Considering the proposed objective, scientific production I is an observational study, composed of 42 children and adolescents between 7 and 13 years of age, of both sexes, distributed in 3 groups. The G1 group was composed of 19 victims of child sexual violence; the G2 group was composed of 10 children with cancer; the G3 group consisted of 13 children who were neither sexually victimized or diagnosed with chronic disease. The instruments used were the Zulliger in the Comprehensive System (ZSC) R-Optimized application; Personality Scale for Children (ETPC, EPQ-J); Inventory of Social Skills for Children (SSRS); Intelligence Test (CPM-Raven). For the ZSC, children who were victims of sexual violence differed from non-victims in decreasing GHR and increasing PHR, p, MOR and Bl. These results converged with the results indicated in the other tests, in which G1 differed from other groups when presenting an increase in the variable Psychoticism (ETPC, EPQ-J) and a low repertoire of social skills with a decrease in the variables EG and F2 (SSRS). The results pointed out the validity of the ZSC as a promising instrument in the evaluation of children who are victims of sexual violence, especially in relation to the damages of interpersonal relationships and impaired self-image. Also noteworthy is the increase in the variable Bl, indicating the traumatic effect of sexual violence. Therefore, among the contributions of this research, we highlight the preliminary evidence of ZSC criterion validity in the assessment of Interpersonal Relationships and Self-image of victims of child sexual violence and the indication of specific interventions regarding the weaknesses pointed out by the